2021
DOI: 10.3389/fimmu.2021.693118
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Feed-Forward Loop Triggered by the Complement Component C3 as a Potential Target in Endometriosis

Abstract: The complement system is a major component of humoral innate immunity, acting as a first line of defense against microbes via opsonization and lysis of pathogens. However, novel roles of the complement system in inflammatory and immunological processes, including in cancer, are emerging. Endometriosis (EM), a benign disease characterized by ectopic endometrial implants, shows certain unique features of cancer, such as the capacity to invade surrounding tissues, and in severe cases, metastatic properties. A def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 61 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…Previous studies have shown that the TLR4-C3 axis can regulate intestinal immune responses during chronic colitis ( 41 ). Research byAgostinis C identified the inflammatory feed-foward loop triggered by complement component C3 may serve as a potential therapeutic target for endometriosis ( 42 ). Rijcken E et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the TLR4-C3 axis can regulate intestinal immune responses during chronic colitis ( 41 ). Research byAgostinis C identified the inflammatory feed-foward loop triggered by complement component C3 may serve as a potential therapeutic target for endometriosis ( 42 ). Rijcken E et al.…”
Section: Discussionmentioning
confidence: 99%
“…ROC analysis revealed that four IRGs can be used as potential biomarkers of endometriosis, which also demonstrated the feasibility in terms of the AUC, a signal for endometriosis occurrence. Recently, C3 was considered a candidate diagnostic biomarker of endometrosis, and its expression was correlated with the engraftment of the endometriotic cysts [ 45 ]. The overexpression of VCAM-1 on the peritoneum of endometriosis had been revealed by Schutt et al [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TF-IRG network could be used to present novel prospective molecular mechanisms underlying the development of tumors [ 45 ]. However, studies of the regulatory mechanisms underlying TFs and IRGs in endometriosis are still in progress.…”
Section: Discussionmentioning
confidence: 99%
“…The key step for activating the complement system by recognizing non self-molecules is to activate the central C3 component through the classical pathway (antibody mediated), lectin pathway or alternative pathway ( 91 ). C3 is also present in the epithelial cells of the endometrium ( 92 ). Activation of C3 on the cell surface can stimulate the formation of membrane attack complexes on NEUs and target cells, resulting in cell damage and cell lysis, but other host cells are protected by membrane binding regulatory molecules such as CD46, CD55 and CD59 ( 93 ).…”
Section: Reciprocal Interactions Between Immunity Endometrium and Mic...mentioning
confidence: 99%